β-catenin accumulation and mutation of the CTNNB1 gene in hepatoblastoma - Bläker, Hendrik; Hofmann, Walter J.; Rieker, Ralf Joachim; Penzel, Roland; Graf, Matthias; Otto, Herwart F. (Genes, chromosomes & cancer, 1999)
Hepatoblastoma is a rare malignant tumor of the liver that occurs in children at an average age of 2 to 3 years. Epidemiologic studies have shown an increased frequency of this tumor type in families affected by adenomatous polyposis coli. In addition to the epidemiologic data, molecular genetic studies suggest that inactivation of the APC tumor suppressor may be involved in hepatoblastoma tumorigenesis. A major function of APC is the downregulation of beta-catenin, a transcription-activating protein with oncogenic potential. In an ongoing immunohistochemical study of beta-catenin expression in sporadic cases of tumor types that are associated with adenomatous polyposis coli, we observed increased beta-catenin levels in the cytoplasm and in the nuclei of three investigated hepatoblastomas. Sequencing of exon 3 of the beta-catenin gene (CTNNB1) revealed an activating mutation in one of the tumor samples. Our data indicate for the first time that beta-catenin accumulation may play a role in the development of hepatoblastoma and that activating mutations of the beta-catenin gene may substitute biallelic APC inactivation in this tumor type. Genes Chromosomes Cancer 25:399-402, 1999.